Resilience – an emerging paradigm of danger or of hope?. Issue 1 (28th January 2014) - I. Sudmeier-Rieux, Karen
Abstract : Purpose: – The purpose of this paper is to explore whether "resilience" offers any positive inputs to international discourse in the field of disaster risk reduction and climate change adaptation and if so, what recommendations can be made for further research on the topic. Design/methodology/approach: – In addition to an in-depth literature review, observations on resilience were made based on interdisciplinary research conducted in Nepal 2008-2011 with landslide affected communities, to map local understandings of resilience in contrast to issues of risk and vulnerability. Findings: – Resilience has the potential to offer a more systemic and cross-cutting approach to disaster risk reduction, climate change adaptation and the humanitarian sector. However, it needs to be assessed critically as one attribute of sustainable development, not as a lesser substitute. Originality/value: – This paper provides new insights to the emerging contrast between proponents and critics of the resilience paradigm with recommendations for avoiding potential dangers that this paradigm brings.